The summer of bitter and sweet - Ferguson, Jenny, 1985- (Heartdrum, an imprint of HarperCollinsPublishers, 2022)
"Lou has enough confusion in front of her this summer. She'll be working in her family's ice-cream shack with...her former best friend, King, who is back in their Canadian prairie town after disappearing three years ago...But when she gets a letter from her biological father...Lou immediately knows that she cannot meet him...While King's friendship makes Lou feel safer...when her family's business comes under threat, she soon realizes that she can't ignore her father forever"--